'n Evaluasie van Pharos Aanleerderwoordeboek vir skole/Learner's Dictionary for Schools en Longman-HAT Afrikaans Dictionary and Grammar for English Speakers in 'n Afrikaanse taalverwerwingskursus op universiteitsvlak - Claassen, Dané (Lexikos, 2015)
An evaluation of Pharos Aanleerderwoordeboek vir skole/Learner's Dictionary for Schools and Longman-HAT Afrikaans Dictionary and Grammar for English Speakers in an Afrikaans language learning course at university level. Research shows that a well-chosen dictionary is the next best resource after the facilitator to enhance the language learning process. There are currently no monolingual or bilingual learner's dictionaries specifically targeting foreign learners who are learning Afrikaans at a tertiary level. Educators and facilitators must thus compensate by prescribing learner's dictionaries such as Pharos's Aanleerderwoordeboek vir skole/Learner's Dictionary for Schools and Longman-HAT's Afrikaans Dictionary and Grammar for English Speakers for these learners. In this article these two dictionaries are being evaluated empirically and qualitatively to determine if there is a need for the composition of a learner's dictionary which specifically targets foreign learners learning Afrikaans at a university level. These specific two learner's dictionaries are being evaluated because they are prescribed for foreign students respectively at, the University of Stellenbosch and the Nelson Mandela Metropolitan University. The degree to which a certain dictionary succeeds in satisfying the lexicographical needs of a specific target group does not only depend on the lexicographer, but also on the target group itself. The current dictionary culture in South Africa is brought to light through reviewing the Curriculum Assessment Policy Statements (CAPS), which is currently being followed in the South African school system. On this basis, suggestions are made for formal dictionary education at tertiary level which includes general and specific dictionary education.